Controllable-multichannel carbon nanofibers-based amorphous vanadium as binder-free and conductive-free electrode materials for supercapacitor. (21st December 2016) - Huang, Guofang; Li, Chunping; Bai, Jie; Sun, Xingwei; Liang, Haiou
Abstract: Multichannel carbon nanofibers-based amorphous vanadium (VMCNFs) was fabricated via electrospinning technology and calcination process. The amorphous V2 O5 were homogeneous dispersed in the carbon nanofibers with inner hollow channels. One-dimensional structure nanomaterials with a compound inner fistulous pore construction promote the electrochemical property due to the synergistic effect between the hollow inner channels and carbon nanofibers with amorphous vanadium. With changing the addition amount of PS acting as a porogen, the optimized VMCNFs-0.5, in which the molar ratio of VO(acac)2 /styrene monomer (SM) was 0.5, exhibited a high specific capacitance of 739 F g −1 at 0.5 A g −1 and good cycling performance with 80.3% capacitance retention after 1500 cycles. Thus this novel method can provide an acceptable idea for practical applications in energy storage. Highlights: Composite carbon fibers (VMCNFs) had been prepared. VMCNFs performed excellent electrochemical property. The perfect property derived from hollow channels and vanadium in carbon fibers. VMCNFs exhibited good specific capacitance and long cycle life.